2004
DOI: 10.1002/jbm.a.30115
|View full text |Cite
|
Sign up to set email alerts
|

Differential effect of a bone morphogenetic protein‐7 (OP‐1) on primary and revision loaded, stable implants with allograft

Abstract: Morselized impacted bone allograft is often used to reconstruct the bone bed in the revision of failed total joint arthroplasties. We hypothesized that addition of the bone morphogenetic protein OP-1 (BMP-7) to bone allograft would improve early implant fixation. We inserted one loaded 6-mm-diameter titanium implant (surrounded by 0.75-mm gap) in each medial condyle of 24 canines. On one side, the implant was inserted in a controlled experimental revision setting resembling the clinical revision situation. A p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
30
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 33 publications
2
30
0
Order By: Relevance
“…They observed reduced ingrowth into graft mixed with OP-1 if the bone graft had also been treated with clodronate, and they concluded that resorption of the graft is necessary before any substantial new bone formation can take place. Søballe et al (2004) studied the effects of mixing allograft with OP-1 in a canine revision model. Interestingly, they found improved implant fixation without any addition of OP-1 on the side simulating a primary arthroplasty, but they found the opposite on the other side where they had created a situation that was meant to simulate a revision.…”
Section: Discussionmentioning
confidence: 99%
“…They observed reduced ingrowth into graft mixed with OP-1 if the bone graft had also been treated with clodronate, and they concluded that resorption of the graft is necessary before any substantial new bone formation can take place. Søballe et al (2004) studied the effects of mixing allograft with OP-1 in a canine revision model. Interestingly, they found improved implant fixation without any addition of OP-1 on the side simulating a primary arthroplasty, but they found the opposite on the other side where they had created a situation that was meant to simulate a revision.…”
Section: Discussionmentioning
confidence: 99%
“…Applications employing one growth factor have been extensively investigated (Aspenberg et al 1989, Thaller et al 1993, Lind et al 1996b, Zellin et al 1998, Laffargue et al 2000, Tielinen et al 2001, Soballe et al 2004. Applications combining two or more growth factors may be more favorable, due to their additive or synergistic effects on bone formation.…”
mentioning
confidence: 99%
“…The crack revision technique also improved the fixation of nongrafted plasmasprayed HA-coated revision implants and increased new bone formation compared with the technique of reaming where the entire bone shell was removed [2]. We also have shown HA to improve fixation in a noncrack revision experimental animal model compared with Ti6Al4V [19,23,25] and that allograft packed into a periimplant gap improves fixation in a variety of experimental and clinical settings [4,7,9,22,23,[27][28][29].…”
Section: Introductionmentioning
confidence: 92%
“…Bone from different canine donors was mixed and portioned into 1-cm 3 aliquots, stored in sterile containers, and refrozen to À20°C. During surgery, the bone allograft was inserted into the revision cavity using a specially modified curette and cylindrical impaction tool [22,23]. The procedure was repeated in approximately three to four steps until the entire revision cavity was filled with tightly packed allograft.…”
Section: Bone Allograftmentioning
confidence: 99%